On archaic oxytonesis in Slovene Ter dialect - Kapović, Mate (Slovenski jezik / Slovene Linguistic Studies, 2023)
The paper discusses the oxytonic mokȁ ‘flour’, bradȁ ‘beard’ type accent in the central Prosnid–Porčinj–Subid belt of the Ter dialect based on the material from Janoš Ježovnik‘s 2022 monograph. This type of accent is often interpreted in Slovenian accentology and dialectology as being innovative because the retraction of the short accent from a final open syllable to a preceding length is usually regarded as a Common Slovene innovation. This type of accent is found in the following types of forms: words like mokȁ, words like gensg kjučȁ, words like vinȍ, adjectives like mladȁ and participles like treslȁ (the oldest speakers still seem to preserved inconsistent length in these forms). The progressive shift of the *jùžina ‘lunch’ > Porčinj južȅ̥na type is clearly a distinct process and the infinitival opposition of *pećȉ but *rásti (with the innovative accent in the second longroot type) is to be connected with a typical Kajkavian-Čakavian-Western Štokavian non-phonetic ‘retraction’ of accent in certain forms (such as the infinitive). The author concludes that central (Prosnid–Porčinj–Subid) Ter dialects (and some other Slovene dialects like Kobarid) preserve the old Slavic final accent in open syllables even after the originally long root.